Suburothelial hemorrhage masquerading as renal neoplasms: a case report of antopol Goldman lesion - Vijay, Tanvi; Gyan Saurabh; Singh, Ranvir; Singh, Smita (International Surgery Journal, 2023)
Renal cell carcinoma (RCC), which accounts for 2-3% of all adult malignancies, is one of the most lethal urologic cancers. They are sporadic in the majority of cases with 4-6% being familial. They are adenocarcinomas arising from renal tubular epithelial cells. They can present with symptoms of loin pain, palpable mass and haematuria. Another rare presentation is spontaneous perirenal haemorrhage which can be seen in up to 50% of these patients. These patients are also predisposed to increased risk of deep vein thrombosis (DVT) due to prevailing pro-thrombogenic state. Management requires radical nephrectomy for localised disease, targeted therapy and cytoreductive nephrectomy for metastatic RCC. Our patient is adult female who was referred to surgical OPD given her history of gross haematuria and right flank pain for 6 days. She is a known case of DVT on treatment with Warfarin for 4 years. A diagnosis of renal malignancy was made, contrast CT was suggestive of solid mass lesion of the upper pole of calyx likely transitional cell carcinoma (TCC)/papillary RCC. She underwent an urgent radical nephrectomy which showed a hard 5×5 cm lump in the upper pole of the kidney, revealing a clot on the cut section. Post-op HPE showed a large subcapsular hematoma in the upper pole with microscopy showing large areas of haemorrhage surrounded by chronic inflammatory infiltrate, likely Antopol Goldman lesion notorious for its similarity to renal malignancy.